Cone-Beam Computed Tomography: Fractal Analysis of Osseous Changes in Temporomandibular Joint for Rheumatoid Arthritis Patients: A Retrospective Study - S Jayachandran; Nivethitha Nagarajan; M Archana (Indian Journal of Rheumatology)
Background: Rheumatoid arthritis (RA) is a chronic systemic disorder which is autoimmune, inflammatory, and erosive joint disease affecting all the joints in the body. Temporomandibular joint (TMJ) is involved in advanced cases. Trabecular bone of TMJ has higher metabolic activity and shows higher alterations in RA. Aim and Objectives: This study evaluated and compared the trabecular bone changes of TMJ in patients with RA using fractal dimension (FD) analysis on cone-beam computed tomography (CBCT). Materials and Methods: A total of 25 (n = 25) CBCT images of RA patients were included for the study. Mid-sagittal section image was selected, and FD assessment of TMJ was done in the bilateral condylar head, condylar neck, and articular eminence. Statistical Analysis: SPSS® 25.0 (Statistical Package for the Social Sciences) – independent t-test, one-way ANOVA followed by Tukey's post hoc test was used. Results: The condylar head had lowest FD values and condylar neck had highest FD values on both the sides. The overall mean values of FD of condylar head, condylar neck, and articular eminence were lower for female than males. Conclusion: Fractal analysis showed that trabecular bone density was altered in condylar head, condylar neck, and articular eminence. Condylar head was the most affected region followed by articular eminence. Condylar neck was the least affected region in both the sides. Hence, FD analysis of CBCT can potentially be considered as an aid in evaluating osseous changes in trabecular bone architecture of the TMJ and to assess the severity of disease.